2016
DOI: 10.1111/eip.12352
|View full text |Cite
|
Sign up to set email alerts
|

Screening for adolescent suicidality in primary care: the bullying–insomnia–tobacco–stress test. A population‐based pilot study

Abstract: The BITS test could allow the question of suicide risk to be addressed during a routine check-up in primary care but the results need to be validated with 13 to 18-year olds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…These findings confirm and even improve the results of our previous work: in the initial BITS study using a self‐completed questionnaire among 15‐year‐old school students, sensitivity was 75% and specificity 70% (AUC = 0.78) (Binder et al, ). In the TSTScafard detection utility study, sensitivity was 79%, and specificity 55% (Binder et al, ; Binder & Chabaud, ). Our data are in line with those of questionnaires investigating suicidality (even though these questionnaires are designed to assess suicide risk per se, not to alert GPs about the need to ask about suicidality).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These findings confirm and even improve the results of our previous work: in the initial BITS study using a self‐completed questionnaire among 15‐year‐old school students, sensitivity was 75% and specificity 70% (AUC = 0.78) (Binder et al, ). In the TSTScafard detection utility study, sensitivity was 79%, and specificity 55% (Binder et al, ; Binder & Chabaud, ). Our data are in line with those of questionnaires investigating suicidality (even though these questionnaires are designed to assess suicide risk per se, not to alert GPs about the need to ask about suicidality).…”
Section: Discussionsupporting
confidence: 90%
“…As a means of alerting about a history of suicidality, the performance of the BITS‐test in a primary care population of 13‐to‐18‐year‐olds consulting a GP was similar to that of a self‐administered questionnaire completed by 15‐year‐olds in a school setting (Binder et al, ). The ROC curve indicated that a score equal or above 3 on the BITS test showed good sensitivity (66%) and high specificity (83%) for the identification of suicidality in this population.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Several tools have been validated and recommended in France; some can be memorized, such as the test to screen suicide risks and the HEADSS psychosocial interview guide; [17] others such as the ADRSp are self-administered questionnaires designed to evaluate depressive tendencies. [27][28][29]…”
Section: Comparison To the Literaturementioning
confidence: 99%